Does farm animals experience emotions and feelings? - Machado, Miguel (2019)
In recent years, there has been a great increase in the interest of "emotion" and how it can be studied and translated from animals. Emotions arise when the brain receives an external stimulus, while the feeling is a response to emotion and concerns how the individual feels before that emotion. Emotional states do not exist to be locked within an individual. Emotions are expressed in some way and have great importance for the welfare of animals, especially within the farm animal production chains. The affective side of emotions is more difficult to be studied, however, it takes an effort to evaluate what is observable, registrable and measurable: behavioral and physiological measures that may indicate positive and negative emotional states. It is possible to use behavioral and even physiological information to analyze the feeling and, especially, the immediate emotion that triggers it in animals. The aim of this article is to review the concepts and researches on emotions and feelings in farm animals that may be related to the expression of emotions.